KEANEKARAGAMAN JENIS BURUNG DI WILAYAH TAMAN KOTA SPATODEA DAN TABEBUYA, JAKARTA SELATAN - Amelia (Bioma, 2022)
Urban parks in South Jakarta are the main component of green open spaces which act as habitat for birds in the cities. Aim of this study was to determine the diversity of bird species around the South Jakarta City Park. The research was conducted in October-November 2021 in the city parks of Spatodea and Tabebuya, South Jakarta. Bird data collection used the point count method, while plant data collection used an inventory system. Results showed that the Tabebuya Park location had 9 species of birds from 8 different families, while in Spatodea Park there were 8 bird species found. The Tabebuya City Park was found to have medium species diversity index value, medium evenness index value and low dominance value index. Spatodea city park had a low value index of species diversity, low evenness value index, and low dominance value index. The highest number of bird species obtained was 7 species in total. The results showed that the urban park area in South Jakarta had low to moderate range of bird species diversity. This could happen because birds in urban landscapes tended to be more sensitive to the presence of certain stratification of vegetation, especially tree stratification.